A STUDY ON RECTANGULAR MICROSTRIP ANTENNA LOADED WITH OPEN STUBS - Hiremath, Basavalinga Swamy (Journal of Advanced Research in Information Technology, Systems and Management, 2021)
In this paper a double band microstrip reception apparatus is acknowledged by setting open circuit stub on the edges of the fix. At the point when the stub length is taken to be almost quarter wave long, it offers capacitive and inductive impedance around the reverberation recurrence of the fix and acknowledges double recurrence reaction. In this paper, a detail examination for the impact of stub on the double band reaction of rectangular microstrip reception apparatus is introduced. The surface current conveyances and the reverberation bend plots were examined. It was seen that the stub adjusts the key and higher request symmetrical mode reverberation frequencies of the fix and acknowledges double recurrence reaction. With an expansion in stub length the bearings of surface flows are adjusted, which gives broadside radiation design at the double frequencies. The plan of thunderous length at double frequencies regarding stub measurements is proposed and they concur inside 5% with that of the mimicked results. an open stub stacked rectangular microstrip reception apparatus (OSRMSA) is planned, manufactured and examined. This reception apparatus reverberates from 2.23 GHz to 9.93 GHz of frequencies and displays multiband activity with a greatest addition of about 4.81GHz. A middle took care of 50ω microstripline feed game plan is utilized to energize receiving wire. The other receiving wire boundaries like return misfortune, transfer speed and radiation design are examined and talked about. This reception apparatus might be valuable for C and S band applications . How to cIte thIs artIcle: Pallavi B, Swamy B, Sadhana C. A Study on Rectangular Microstrip Antenna Loaded with Open Stubs. J Adv Res Info Tech Sys Mgmt 2020; 4(2): 1-7.